2005
DOI: 10.3171/jns.2005.103.1.0156
|View full text |Cite
|
Sign up to set email alerts
|

Active immunotherapy for advanced intracranial murine tumors by using dendritic cell-tumor cell fusion vaccines

Abstract: These data indicate a strategy to achieve an antitumor response against tumors in the central nervous system that is highly focused from both immunological and anatomical perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 44 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…Although this vaccine modality is exceptional for its capacity to bypass the constraints of exogenous processing to present endogenous tumor proteins in both MHC Class I-and II-restricted, and highly costimulatory contexts, vaccination has consistently benefited from parenteral codelivery of third signals for maximized therapeutic efficacy. Among tested parenteral third signals, IL-12 and OX40 ligating monoclonal antibody (mAb) have proved particularly effective (10,11). Here, we show that fusion hybrid vaccination plus a single TLR agonist induces no detectable therapeutic antitumor immunity, whereas vaccination plus paired TLR agonists show powerful therapeutic responses against established lung metastases derived from the MCA205 sarcoma.…”
Section: Introductionmentioning
confidence: 92%
“…Although this vaccine modality is exceptional for its capacity to bypass the constraints of exogenous processing to present endogenous tumor proteins in both MHC Class I-and II-restricted, and highly costimulatory contexts, vaccination has consistently benefited from parenteral codelivery of third signals for maximized therapeutic efficacy. Among tested parenteral third signals, IL-12 and OX40 ligating monoclonal antibody (mAb) have proved particularly effective (10,11). Here, we show that fusion hybrid vaccination plus a single TLR agonist induces no detectable therapeutic antitumor immunity, whereas vaccination plus paired TLR agonists show powerful therapeutic responses against established lung metastases derived from the MCA205 sarcoma.…”
Section: Introductionmentioning
confidence: 92%
“…Current treatment methods include surgical resection, radio-surgical, external irradiation, chemotherapy (Cheng et al, 2005;Stupp et al, 2006;Wen et al, 2006), and biological therapy (Kjaergaard et al, 2005). Despite recent advances in diagnostics and treatments, prognosis for patients with this disease remains poor (Ng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…36,39,51,52 Others have shown that DC-vaccination combines favorably with radiotherapy by increasing radio-sensitivity of tumor cells and up-regulating the expression of MHC antigens in animal models. 27 In contrast, Chang et al 43 argue that the development of radiotherapy-induced mutant tumor cells, immunologically diverse from the ones obtained during surgery, may render vaccines inactive against residual or relapsed tumors.…”
Section: Timing Of Vaccinationmentioning
confidence: 99%
“…26 Other research has focused on the interaction between other treatment modalities, such as radiotherapy, and DC-vaccinations in murine brain tumor models. 27 It was found that the combination of radiotherapy and DC-vaccinations can enhance the effect of the latter and improve outcomes. This was attributed to irradiation-induced upregulation of MHC molecules in tumor cells, which rendered them better immunological targets.…”
Section: Origin and Research Basis For Efficacy Of The Productmentioning
confidence: 99%